Economic Crimes: Factors Responsible For Rampant Fraud And Corruption In Kenya - Onyango, Omboto John (Advances in Social Sciences Research Journal, 2018)
On 28th June, 2018 President Uhuru Kenyatta rightfully declared that there would be no sacred cows in the war against corruption in Kenya. This declaration came at a time when fraud and corruption is so common place to an extent that an occurrence is no longer news. In fact, as if competing for a trophy, every regime have had at least a mega scandal associated with it, thus continuously draining the treasury at the detriment of any meaningful economic growth and affordable cost of living for the citizens; majority of whom are destitute. Among the many outstanding scandals that have depleted billions of shillings from the tax payers associated with the three latest regimes are Goldenberg and Anglo leasing scandals, and the National Youth Service scams. This paper introduces the concept of fraud and corruption and discusses the types of corruption in Kenya, the red flags of fraud, mechanisms of controlling frauds and the factors that have over the years been responsible for the widespread corruption which has continued to plague the country.